GUIDE FOR AUTHORS - ECOSISTEMAS Y RECURSOS AGROPECUARIOS, ECOSISTEMAS Y (Ecosistemas y Recursos Agropecuarios, 2015)
Ecosistemas y Recursos Agropecuarios (Ecosystems and Agricultural Resources) is a quarterly journal that has been published by the Universidad Juárez Autónoma de Tabasco (Juárez Autonomous University of Tabasco) since 2014. It publishes results of original and unpublished research in the form of Scientific Arti- cles, Scientific Notes, Review Articles and Letters to the Editor, related to the Agricultural Sciences, Animal Science, Environmental Sciences, Wildlife, Natural Resource Use and Conservation, and Ecology. The journal is included in the Index of Mexican Journals of Scientific Research and Technology (CONACyT), SciELO Citation Index, SciELO Mexico and other national and international indexes; it is dis- tributed to national and international higher education institutions and research centers.